2011
DOI: 10.1002/cbic.201000634
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression and Purification of Fungal Galactose Oxidase in Escherichia coli and Use for Analysis of a Saturation Mutagenesis Library

Abstract: Galactose oxidase (GO) displays broad primary alcohol substrate specificity and so offers potential for engineering new substrate specificity by directed evolution. Producing variant libraries of sufficient complexity ideally requires expression of functional protein in a host such as Escherichia coli. Wild-type GO is produced by the fungus Fusarium graminiarum and is expressed poorly in E. coli. We introduced silent mutations within codons 2-7 of the mature GO coding sequence to enhance GO translation and hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 59 publications
(63 reference statements)
3
20
0
Order By: Relevance
“…The additional silent mutations, along with optimized cultivation conditions, increased GAO productivity over 20 times to 240 mg L -1 [92]. Systematic comparison of GAO expression in E. coli and P. pastoris confirmed that the modifications to codon sequence reported by Sun et al (2001) [24] increased GAO expression in E. coli, but did not improve GAO expression in P. pastoris [13].…”
Section: Heterologous Expressionsupporting
confidence: 57%
See 1 more Smart Citation
“…The additional silent mutations, along with optimized cultivation conditions, increased GAO productivity over 20 times to 240 mg L -1 [92]. Systematic comparison of GAO expression in E. coli and P. pastoris confirmed that the modifications to codon sequence reported by Sun et al (2001) [24] increased GAO expression in E. coli, but did not improve GAO expression in P. pastoris [13].…”
Section: Heterologous Expressionsupporting
confidence: 57%
“…GAO production in E. coli was further increased by introducing silent mutations in codons two to seven [92], in addition to the six substitutions reported by Sun et al (2001) (Table 5) [24].…”
Section: Heterologous Expressionmentioning
confidence: 98%
“…[17,18] Examples of its application include improved themostability, [88] tolerance to organic solvents, [89] strengthened proteinprotein interactions, [90] altered substrate promiscuity/specificity, [91,92] enhanced enzymatic activity, [93] and inversion of enantioselectivity. [94,95] In the directed evolution of catalytic function, a starting gene is mutagenized to create a library of variants, which is screened for enzymes with an improvement of the sought-after property (stability, substrate specificity, activity, etc.).…”
Section: Directed Evolutionmentioning
confidence: 99%
“…Expression has been increased by using directed evolution and site directed mutagenesis [21][23]. Higher yields were obtained by expression of the wild type enzyme in P. pastoris [15], [24][27] and A. nidulans [28].…”
Section: Introductionmentioning
confidence: 99%